The Placebo Effect in Digital Games - Alena Denisova (Symposium on Computer-Human Interaction in Play (CHI Play), 2015)
Play-testing of digital games is a crucial part of any game development process, used to gather feedback about the game and correct any existing and potential flaws with the design. However, due to the nature of human subject testing, the feedback being collected in such experiments is prone to biases. Players' expectations play a great role in dictating their gaming experience, which means the information players receive before trying a new game, as well as the knowledge they already possess, may affect their perception and experience of the game. Two studies were conducted in order to evaluate how priming players to expect a game technology can positively influence their experience. The results supported the hypothesis that even basic instructions can change players' perception of the game, and lead to a higher level of perceived immersion when knowing that the game contains an improved feature, the adaptive artificial intelligence (AI), while it is not present in the game.